Adaptive 3D Image‐Guided Brachytherapy: A Strong Argument in the Debate on Systematic Radical Hysterectomy for Locally Advanced Cervical Cancer. (8th April 2013) - Mazeron, Renaud; Gilmore, Jennifer; Dumas, Isabelle; Champoudry, Jérôme; Goulart, Jennifer; Vanneste, Ben; Tailleur, Anne; Morice, Philippe; Haie‐Meder, Christine
Abstract : Learning Objectives: Evaluate control rates of IGABT combined with CCRT for the treatment of locally advanced cervical cancer. Describe survival outcomes in patients treated with IGABT combined with CCRT for locally advanced cervical cancer. Describe toxicities in patients treated with IGABT combined with CCRT for locally advanced cervical cancer. Purpose: To evaluate the outcomes of patients with locally advanced cervical cancer treated with three‐dimensional image‐guided brachytherapy (IGABT) after concomitant chemoradiation (CCRT). Materials and Methods: Data from patients treated with CCRT followed by magnetic resonance imaging‐guided or computed tomography‐guided pulsed‐dose‐rate brachytherapy, performed according to the Groupe Européen de Curiethérapie–European Society for Radiotherapy and Oncology guidelines, were reviewed. At first, stage I or II patients systematically underwent radical hysterectomy or were offered a randomized study evaluating hysterectomy. Then, hysterectomy was limited to salvage treatment. Results: Of 163 patients identified, 27% had stage IB, 57% had stage II, 12% had stage III, and 3% had stage IVA disease. The mean dose delivered (in 2‐Gy dose equivalents) to 90% of the high‐risk clinical target volume was 78.1 ± 9.6 Gy, whereas the doses delivered to organs at risk were maintained under the usual thresholds. Sixty‐one patients underwent a hysterectomy. Macroscopic residual disease was found in 13 cases. With a median follow‐up of 36 months (range, 5–79 months), 45 patients had relapsed. The 3‐year overall survival rate was 76%. Local and pelvic control rates were 92% and 86%, respectively. According to the Common Toxicity Criteria 3.0, 7.4% of patients experienced late grade 3 or 4 toxicity. Most of those had undergone postradiation radical surgery (2.9% vs. 14.8; p = .005). Conclusion: IGABT combined with CCRT provides excellent locoregional control rates with low treatment‐related morbidity, justifying the elimination of hysterectomy in the absence of obvious residual disease. Distant metastasis remains an important first relapse and may warrant more aggressive systemic treatment. Abstract : The outcomes of patients with locally advanced cervical cancer treated with three‐dimensional image‐guided brachytherapy after concomitant chemoradiation were evaluated. An excellent locoregional control rate with low treatment‐related morbidity was observed, justifying the elimination of hysterectomy in the absence of obvious residual disease.